Application of ultra-low-dose CT in 3D printing of distal radial fractures. Issue 135 (February 2021) - Xiao, Mengqiang; Zhang, Meng; Lei, Ming; Hu, Xiaolu; Wang, Qingshan; Chen, Yanxia; Ye, Jingzhi; Xu, Rulin; Chen, Jun
Abstract: Purpose: To explore the effect of ultra-low-dose computed tomography (CT) on three-dimensional (3D) printing models and the diagnosis of wrist fractures. Method: This study enrolled 76 patients with distal radial fractures (DRFs). All patients underwent 320-row detector CT and were divided randomly into two groups. In Group A, 38 patients were scanned with the standard-dose protocol using a tube voltage of 120 kV and current of 100 mA. In Group B, 38 patients were scanned with the ultra-low-dose protocol using a tube voltage of 80 kV and current of 10 mA. For objective image quality assessment, the noise, CT number, signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR) were measured. Subjectively, two experienced orthopaedic surgeons blinded to the scan parameters evaluated the clarity of the 3D printing model and fracture line using a 3-point scale (the diagnosis was considered acceptable with scores ≥2). The mean radiation dose was calculated. The diagnostic performances for the fractures between the two groups were compared. Results: The effective radiation dose was significantly reduced by 97.1 % in Group B, compared to Group A (0.28 ± 0.05 vs . 9.75 ± 2.23 μSv, respectively). Quantitative objective image quality parameters ( e.g., CNR, SNR, and CT numbers) were higher in the standard-dose group ( p  < 0.001). However, there was no difference in subjective scoring of the 3D printing model. Although the fracture line score was higher in Group A (2.92±0.27 vs . 2.16 ± 0.37; p  < 0.001), the diagnostic performance of the two groups was consistent (all scores ≥2). There were no statistically significant differences in the sensitivity, specificity or accuracy between standard-dose group and ultra-low-dose group. Conclusions: The ultra-low-dose protocol effectively reduced the radiation dose by 97.1 %, while maintaining the image quality for diagnosis of DRFs. Therefore, this protocol can meet the needs of 3D printing models for preoperative assessments.